Extraction of Staphyloxanthin from Staphylococcus aureus Isolated from Clinical Sources to Determine its Antibacterial Activity Against other Bacteria - J. AL-Kazaz, Eman; K. Melconian, Alice; J. Kandela, Nuha (Iraqi Journal of Science, 2025)
Fourty three isolates ( 20.7%) characterized as Staphylococcus aureus , were isolated from 207 different clinical sources (blood , nose, , wound , urine , vaginal, ear and eye) in different percentages (30.23, 18.60, 16.28, 13.95, 15.15, 6.96 and 2.33 %), respectively. The staphyloxanthin (STX) production of S. aureus isolate was estimated 72.1% .The optimal conditions for pigment production by S. aureus AE36 , were detected and was noticed that the milk agar medium revealed the highest production of pigment which was estimated to be 165.21unit/cell, at pH 8 for 72 hr at 370C. The Staphyloxanthin pigment was extracted using methanol and was purified partially by organic solvents and Thin Layer Chromatography (TLC). The results revealed three peaks with a highest peak at 450 nm .No antibacterial activity of STX was detected against the bacteria used in this study (Staphylococcus epidermidis, Pseudomonas aeruginosa, Salmonella spp., Shigella spp., Escherichia coli, Klebsiella spp , Proteus spp. Pseudomonas fluorescens , Pseudomonas putida , Staphylococcus aureus).